2023
DOI: 10.3390/fishes8060317
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Spatial Units of Genus Euthynnus from the Eastern Atlantic and the Mediterranean Using Otolith Shape Analysis

Abstract: The shape of sagitta otoliths was used to compare individuals of little tunny (Euthynnus alleteratus) harvested on board commercial fishing vessels from the coastal areas along the Eastern Atlantic, including the Mediterranean Sea. Fish sampling and selection was designed to cover possible seasonal changes and tuna size. The research encompassed both morphometric and shape analyses of left sagittal otoliths extracted of 504 fish specimens. Four shape indices (Circularity, Roundness, Rectangularity, and Form-Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 87 publications
(114 reference statements)
0
0
0
Order By: Relevance
“…This research is similar. Munoz-Lechuga found some differences in the otoliths of Euthynnus in the Eastern Atlantic and the Mediterranean Sea, based on R language analyses of otoliths [43]. What is more, it has been shown that Decapterus kurroides is not the same stock from the Northern Sulu and Southern Sibuyan Seas [44], based on R language analyses of otoliths.…”
Section: Discussionmentioning
confidence: 98%
“…This research is similar. Munoz-Lechuga found some differences in the otoliths of Euthynnus in the Eastern Atlantic and the Mediterranean Sea, based on R language analyses of otoliths [43]. What is more, it has been shown that Decapterus kurroides is not the same stock from the Northern Sulu and Southern Sibuyan Seas [44], based on R language analyses of otoliths.…”
Section: Discussionmentioning
confidence: 98%